Institutional quality and self-evaluation model in public institutions: a Kenyan case study - Korir, Gerald; Benedek, Petra (Public Finance Quarterly, 2025)
Improving institutional quality is essential for economic growth in developing countries. This study uses the Central Bank of Kenya as a case study to assess the impact of institutional quality management and self-assessment models on public sector performance. Using the ISO 9001:2015 framework, the study focused on principles such as leadership, stakeholder engagement, process approach, and continuous improvement. Survey data from 51 respondents were analyzed using correlation and regression techniques. The results reveal that while several quality management practices are correlated with improved performance, leadership commitment is the only statistically signiﬁcant predictor. Self-assessment models, when embedded in organizational culture and supported by eﬀective leadership, contribute signiﬁcantly to service delivery and strategic alignment. The study highlights the key role of leadership and provides practical guidance for improving quality in public institutions.